Teachers’ and Students’ Perception on Influence of Deviant Behaviours On Academic Performance of Secondary School Students in Lagos State - Agatha C. NWABUEZE1; Olujide A. ADEKEYE1; Gbadebo O. ADEJUMO1; Georgina O. OSAKWE2; Vera N. NWADINOBI3 (Communications of International Proceedings, 2020)
Deviant behaviours among secondary school students has remained a global concern. It is on the increase and is affecting the educational sector across the nation as it is capable of disrupting teaching and learning process in schools. This study investigated the teachers and students’ perceptions of the influence of deviant behaviours on academic performance of senior secondary school students in main land educational district IV of Lagos State. The population was 3,101 participants made up of 290 teachers and 2811 students. Descriptive research design was adopted for the study and simple random sampling was employed to selected 300 participants. The instrument used for the study was “Influence of Deviant Behaviours on Academic Performance of Students (IDBAPS)”. The instrument has a test-retest reliability coefficient of 0.91. Collected data were analyzed using mean and standard deviations and t-test to test the null hypotheses at 0. 05 level of significance. The result of the findings revealed that deviant behaviours influence students’ academic performance. There was no significant difference in the perception of male and female teachers on the influence of deviant behaviours on the academic performance of students but there was no significant difference in junior and senior teachers’ perception of the influence of deviant behaviours on students, academic performance. There was significant difference in male and female students’ perceptions of the influence of deviant behaviours on academic performance. Based on the findings, it was recommended that schools should have functional professional counsellors to minimize deviant behaviours.
Keywords: Perceptions; Teachers; Deviant Behaviour; Academic Performance.